Development of an open-source road traffic noise model for exposure assessment. (December 2015) - Gulliver, John; Morley, David; Vienneau, Danielle; Fabbri, Federico; Bell, Margaret; Goodman, Paul; Beevers, Sean; Dajnak, David; J Kelly, Frank; Fecht, Daniela
Abstract: This paper describes the development of a model for assessingTRA fficN oiseEX posure (TRANEX) in an open-source geographic information system. Instead of using proprietary software we developed our own model for two main reasons: 1) so that the treatment of source geometry, traffic information (flows/speeds/spatially varying diurnal traffic profiles) and receptors matched as closely as possible to that of the air pollution modelling being undertaken in the TRAFFIC project, and 2) to optimize model performance for practical reasons of needing to implement a noise model with detailed source geometry, over a large geographical area, to produce noise estimates at up to several million address locations, with limited computing resources. To evaluate TRANEX, noise estimates were compared with noise measurements made in the British cities of Leicester and Norwich. High correlation was seen between modelled and measured LAeq, 1hr (Norwich: r = 0.85, p = .000; Leicester: r = 0.95, p = .000) with average model errors of 3.1 dB. TRANEX was used to estimate noise exposures (LAeq, 1hr, LAeq, 16hr, Lnight ) for the resident population of London (2003–2010). Results suggest that 1.03 million (12%) people are exposed to daytime road traffic noise levels ≥ 65 dB(A) and 1.63 million (19%) people are exposed to night-time road traffic noise levels ≥ 55 dB(A). Differences in noise levels between 2010 and 2003 were on average relatively small: 0.25 dB (standard deviation: 0.89) and 0.26 dB (standard deviation: 0.87) for LAeq, 16hr and Lnight . Graphical abstract: Highlights: Adaptation of the Calculation of Road Traffic Noise method for exposure assessment. Freely available open-source software (R with PostgreSQL and GRASS GIS). Model estimates compared well to noise measurements (r: ∼0.85–0.95). Noise level exposures modelled for 8.61 million London residents (2003–2010). Over 1 million residents exposed to high daytime and night-time noise levels.